Natural and unnatural history of pulmonary atresia. Issue 5 (1st November 2000) - Leonard, H; Derrick, G; O'Sullivan, J; Wren, C
Abstract : OBJECTIVE: To investigate mortality, cause of death, survival, and quality of life in all types of cardiac malformation with congenital pulmonary atresia. DESIGN: Retrospective analysis. SETTING: The resident population of one health region with a single tertiary referral centre. PATIENTS: All babies with pulmonary atresia live born in 1980 to 1995. MAIN OUTCOME MEASURES: Anatomical classification, total mortality, cause of death, duration of survival, exercise ability. All cases were classified as pulmonary atresia with intact septum (PA-IVS), pulmonary atresia with ventricular septal defect (PA-VSD), or pulmonary atresia with complex cardiac malformation (complex pulmonary atresia). RESULTS: 129 cardiac malformations with congenital pulmonary atresia were identified from 601 635 live births (21.4/100 000): 29 had PA-IVS, 60 had PA-VSD, and 40 had complex pulmonary atresia. Total mortality was 72/129 (56%), with 15 deaths in the first week and 49 in the first year. There were 23 surgical deaths, 33 hospital deaths (not related to surgery), and 16 sudden deaths, 12 of which remained unexplained. The sudden death rate was 29/1000 patient years of follow up. Of the 57 survivors, 39% have exercise ability I or II and 61% III or IV. Definitive surgical repair produced better exercise ability. CONCLUSIONS: Early mortality is high in all types of pulmonary atresia, although survival has improved in recent years. Most children who have not undergone definitive repair have significant exercise limitation.